A performance comparison between cooled and uncooled infrared detectors for thermoelastic stress analysis - Rajic, Nik; Street, Neil (Quantitative infrared thermography, 2014)
This study compares the stress-measurement sensitivity of several commercially available vanadium-oxide microbolometers to a scientific grade cooled indium antimonide imager. The devices were tested under similar conditions on the same mechanically-loaded subjects; one a uniaxially loaded plate containing a circular hole and the other a representative aircraft wing-skin coupon. The microbolometers are shown to consistently outperform the cooled imager for scan durations of 1500 load cycles or more despite having noise equivalent temperature detectivities (NETD) that were inferior by factors of between approximately 2 and 6. This finding is significant in two respects: it suggests that an NETD specification has only limited value as a sensitivity metric for thermoelastic stress analysis and secondly it confirms that microbolometers are able to furnish high-fidelity stress measurements of a type traditionally associated with cooled infrared imagers which are generally more costly to acquire and more cumbersome to use.